2018
DOI: 10.3390/atmos10010001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Extreme Low Temperature Events over Northern China under 1.5 °C and 2.0 °C Warmer Future Scenarios

Abstract: Recently, NCAR (the National Center for Atmospheric Research) released the Community Earth System Model's low-warming simulations, which provided long-term climate data for stabilization pathways at 1.5 • C and 2.0 • C above pre-industrial levels. Based on these data, six extreme low temperature indices-TXn (coldest day), TNn (coldest night), TX10p (cool days), TN10p (cool nights), CSDI (cold spell duration indicator), and DTR (diurnal temperature range)-were calculated to assess the changes in extreme low tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…In this study, the current world is represented by a 30‐years time slice from 1976 to 2005, and the future world is represented by the years 2071–2100 (King et al ., 2017; Sanderson et al ., 2017; Hu et al ., 2018). Temperature extremes indices derived from the HadGHCND gridded daily dataset of near‐surface minimum and maximum temperature observations were used to assess the performance of historical model simulations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the current world is represented by a 30‐years time slice from 1976 to 2005, and the future world is represented by the years 2071–2100 (King et al ., 2017; Sanderson et al ., 2017; Hu et al ., 2018). Temperature extremes indices derived from the HadGHCND gridded daily dataset of near‐surface minimum and maximum temperature observations were used to assess the performance of historical model simulations.…”
Section: Methodsmentioning
confidence: 99%
“…In East Asia, limiting global warming to 1.5°C rather than 2.0°C would reduce the increases in extreme temperature events by 35–46% (Li et al ., 2018a). Over Northern China, stabilizing warming to 1.5°C target instead of 2.0°C may have benefits of avoiding about 31% (6–56%) of the increases in intensity, frequency and duration of extreme low‐temperature events (Hu et al ., 2018). Yohe (2017) showed that in Northern America, a 0.5°C difference from 2.0°C warming level could reduce the aggregated economic losses due to extreme weather events, by approximately 0.35% (0.2–0.65%) of the gross domestic product.…”
Section: Introductionmentioning
confidence: 99%
“…There are two approaches (i.e., the transient and the stabilized approach) to evaluate climate change impacts under the 1.5 • C and 2.0 • C warming levels. The stabilized approach is based on the simulation by the recent Half a Degree Additional Warming, Projections, Prognosis and Impacts project (HAPPI), which is designed to provide stabilized scenarios for the 1.5 and 2.0 • C warming worlds [18,35,36]. The transient method is based on transient climate states extracted from the CMIP5 archive to evaluate climate change impacts at specific global temperature targets.…”
Section: 5 • C and 20 • C Warmer Scenariosmentioning
confidence: 99%
“…In order to assess the avoided impacts (AI) of heatwave under the 1.5 • C warming compared with a 2.0 • C warmer climate, a formula proposed in previous works [35,53] is used:…”
Section: Avoided Impactsmentioning
confidence: 99%
“…They also note changes in South American and African monsoon precipitation related to the volcanic forcing. Hu et al [20] assess projections of extreme low temperature events in Northern China under the IPCC stabilization pathways at 1.5 and 2.0 • C above preindustrial levels and show significant differences in the decrease of intensity, frequency and duration of cold extremes across the two scenarios.…”
mentioning
confidence: 99%